Fashion Brands' Instagram Contents that Influence Customer Purchase Intention - Kautsar, Muhammad; Nuraeni, Shimaditya (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. Social media has changed the way business run, especially in marketing. With the availability of social media, it is easier for business to communicate with their customer. One of social media that influential for business is Instagram. With features that focus on creating contents, Instagram has helped marketers to connect with their customers by creating contents that engage with their customers with the objective to influence their purchase intention. SADE is a local fashion brand from Bandung that use Instagram as its primary marketing channel. In order to gain sales, SADE need to deliver contentsthat able to convert customer interest towards the product into buying the products. Therefore, this research is aim to find out the factors for fashion brands’ Instagram content that significantly influence customer purchase intention. By using questionnaire to collect the data, this research analyzed two independent variables which is product presentation and perceived quality towards purchase intention. The data were collected with the amount of 212 respondents, in where the respondents came from Bandung and Jakarta with the age of between 18 - 37 years old and actively using Instagram. By using multi-linear regression to find out the relationship of each independent variables, the research concluded that variables that have significant effect on customer purchase intention are product presentation and perceived quality.Keywords: Instagram, Social Media, Fashion Brand, Instagram Contents, Purchase Intention